Macrogenome-based study on the mechanism of Bacillus velezensis SX13 in regulating rhizophere environment and cucumber growth under different cultivation environments - Junzheng Wang; Mingfei Yang; Jing Wang; Peng Wang; Jiaqi Pan; Fei Ma; Xiaohui Hu (Horticultural Plant Journal)
Microbial activities are the dynamic core of nutrient cycling in organic substrates, and the exploitation of plant growth-promoting rhizobacteria strains contributes to sustainable agricultural development. This study aimed to investigate the effect and mechanism of Bacillus velezensis SX13 in nutrient cycling and plant promotion under different substrate supply conditions. The effects of reduced substrate amount (sCK) and inoculation of SX13 strain under both substrate supply conditions (Bv and sBv) on rhizosphere microenvironment and plant growth were investigated using conventional substrate amount (CK) as a control. Results showed no significant difference in the α-diversity indexes (Chao1 and Shannon) of the rhizospheric microbial community among the four treatments. However, nonmetric multidimensional scaling analysis and principal coordinate analysis revealed that compared with CK treatment, the inoculation of SX13 strain and reduced substrate supply reshaped the β-diversity structure of microbial communities. Furthermore, inoculation with B. velezensis SX13 under both substrate supply conditions increased the abundance of Proteobacteria (1.64%–2.46%), Acidobacteria (14.09%–43.07%), and Firmicutes (179.29%–861.29%). The results of the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis showed that the metabolic pathway with the highest abundance of enriched genes was also the pathway with the most enriched differential genes caused by reducing substrate supply or inoculation of B. velezensis SX13. The rhizosphere inoculation of B. velezensis SX13 significantly up-regulated the top genes related to carbohydrate esterases, carbohydrate binding modules, glycoside hydrolases, glycoside transferases, and polysaccharide lyases. As a result, the activities of carbon and nitrogen cycle-related enzymes such as cellobiohydrolase, β-glucosidase, urease, l-leucine amino peptidase, and β-1,4-N-acetylglucosaminidase were increased, which in turn accelerated nutrient cycling. B. velezensis SX13 and its mediated improvement of the rhizospheric microenvironment resulted in the up-regulation of root CsNRT family genes (such as CsNRT1.1, CsNRT1.4a, CsNRT1.4b, CsNRT1.5a, CsNRT1.5b, CsNRT1.5c, and CsNRT1.8), which accelerated nitrogen uptake, accumulation, and utilization efficiency and ultimately improved the yield and quality of cucumber. The effect of SX13 strain was more stable and efficient under conventional substrate supply conditions than under reduced substrate supply conditions.